1999
DOI: 10.1136/adc.80.6.500
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of specialist health visitor intervention for failure to thrive   Commentary

Abstract: Aims-To determine whether home intervention by a specialist health visitor aVects the outcome of children with failure to thrive. Methods-Children referred for failure to thrive were randomised to receive conventional care, or conventional care and additional specialist home visiting for 12 months. Outcomes measured were growth, diet, use of health care resources, and Bayley, HAD (hospital anxiety and depression), and behavioural scales. Results-Eighty three children, aged 4-30 months, were enrolled, 42 receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…A significant proportion of children who fail to thrive show catch-up growth (e.g., Kristiansson & Fa$ lstro$ m, 1987), suggesting that the chronic problems experienced by Puckering and colleagues ' sample may have been particularly severe. Wright, Callum, Birks, and Jarvis (1998) found that health visitor intervention was related to better physical outcomes following failure to thrive, but there is little evidence that such intervention has a positive impact on cognitive outcomes following FTT (Raynor, Rudolph, Cooper, Marchant, & Cottrell, 1999). Moreover, the majority of infants who fail to thrive are not identified or referred (Batchelor & Kerslake, 1990 ;Skuse et al, 1992), and so would not experience any potential benefits from hospital-or community-based intervention.…”
Section: Failure To Thrive and Child Psychological Developmentmentioning
confidence: 95%
“…A significant proportion of children who fail to thrive show catch-up growth (e.g., Kristiansson & Fa$ lstro$ m, 1987), suggesting that the chronic problems experienced by Puckering and colleagues ' sample may have been particularly severe. Wright, Callum, Birks, and Jarvis (1998) found that health visitor intervention was related to better physical outcomes following failure to thrive, but there is little evidence that such intervention has a positive impact on cognitive outcomes following FTT (Raynor, Rudolph, Cooper, Marchant, & Cottrell, 1999). Moreover, the majority of infants who fail to thrive are not identified or referred (Batchelor & Kerslake, 1990 ;Skuse et al, 1992), and so would not experience any potential benefits from hospital-or community-based intervention.…”
Section: Failure To Thrive and Child Psychological Developmentmentioning
confidence: 95%
“…However, considering that randomised trials of interventions for FTT have failed to demonstrate convincing effects in these areas,34 35 it seems unlikely that clinical interventions have masked the impact on psychological development and educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…We received data on children enrolled in a randomised controlled trial of health visitor intervention in failure to thrive,3 calculating anthropometric indices for all children using five methods as shown in table 1. For calculation of the three first methods, median height and weight were taken as the 50th centile of the 1990 growth standards 4.…”
Section: Methodsmentioning
confidence: 99%